Bumetanide Rescues Aquaporin-4 Depolarization via Suppressing β-Dystroglycan Cleavage and Provides Neuroprotection in Rat Retinal Ischemia-Reperfusion Injury. (1st February 2023) - Chen, Chunyan; Fan, Ping; Zhang, Lirong; Xue, Kaige; Hu, Jiaheng; Huang, Juan; Lu, Weitian; Xu, Jin; Xu, Shiye; Qiu, Guoping; Ran, Jianhua; Gan, Shengwei
Highlights: Bumetanide rescues aquaporin-4 depolarization in a rat retinal I/R injury model. BU suppresses AQP4 protein/mRNA and β-DG mRNA expression. BU reduces retinal apoptotic cells and downregulates p-ERK and MMP9 expression. BU suppresses β-DG cleavage, in part, via the ERK/MMP9 pathway. BU protects against retinal cytotoxic edema in a rat retinal I/R injury model. Abstract: Aquaporin-4 (AQP4) regulates retinal water homeostasis and participates in retinal oedema pathophysiology. β-dystroglycan (β-DG) is responsible for AQP4 polarization and can be cleaved by matrix metalloproteinase-9 (MMP9). Retinal oedema induced by ischemia–reperfusion (I/R) injury is an early complication. Bumetanide (BU) has potential efficacy against cytotoxic oedema. Our study investigated the effects of β-DG cleavage on AQP4 and the roles of BU in a rat retinal I/R injury model. The model was induced by applying 110 mm Hg intraocular pressure to the anterior eye chamber. BU and U0126 (a selective ERK inhibitor) were intraperitoneally administered 15 and 30 min, respectively, before I/R induction. Rhodamine isothiocyanate extravasation detection, quantitative real-time PCR, transmission electron microscopy, hematoxylin-eosin staining, immunofluorescence staining, western blotting, and TUNEL staining were performed. AQP4 lost its polarization in the retinal perivascular domain as a result of β-DG cleavage. BU rescued AQP4 depolarization, suppressed AQP4 protein expression, attenuated retinal cytotoxic oedema, and downregulated β-DG and AQP4 mRNA expression. BU suppressed glial responses and mitochondria-mediated apoptotic protein expression, including that of Caspase-3 and Cyto C, raised the Bcl-2/Bax ratio, and lowered the number of apoptotic cells in the retina. Both BU and U0126 downregulated p-ERK and MMP9 expression. Thus, BU treatment suppressed β-DG cleavage, recovered AQP4 polarization partially via inhibiting ERK/MMP9 signaling pathway, and possess potential neuroprotective efficacy in the rat retinal ischemia–reperfusion injury model.